2018
DOI: 10.1186/s12871-018-0535-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a combination “lymphocyte apoptosis model” to predict survival of sepsis patients in an intensive care unit

Abstract: BackgroundA major challenge in sepsis intervention is unclear risk stratification. We postulated that a panel of biomarkers of lymphocyte apoptosis and immune function, termed the “lymphocyte apoptosis model,” would be an effective tool for predicting 28-day survival for sepsis patients.MethodsA total of 52 consecutive sepsis patients were enrolled. Peripheral blood samples were collected on day 1 of admission for quantification of biomarkers of lymphocyte apoptosis and immune function, including lymphocyte co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 44 publications
(40 reference statements)
0
34
0
Order By: Relevance
“…Figure 1 shows the scheme of the systematic review. A total of 3,397 articles were screened by title and abstract in the databases analysed (485 in MEDLINE, 1,254 in Scopus and 1,658 in EMBASE), and 44 articles were studied for full‐text analysis 15‐58 . Of these, 12 were excluded because not all the patients were diagnosed with sepsis, 15‐26 seven did not develop a predictive model, 27‐33 in four the outcome to be predicted was not mortality, 34‐37 in another four they did not use their own data, 38‐41 two evaluated only one specific microorganism and not sepsis in general, 42,43 and one applied Machine Learning techniques, 44 which were not considered in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the scheme of the systematic review. A total of 3,397 articles were screened by title and abstract in the databases analysed (485 in MEDLINE, 1,254 in Scopus and 1,658 in EMBASE), and 44 articles were studied for full‐text analysis 15‐58 . Of these, 12 were excluded because not all the patients were diagnosed with sepsis, 15‐26 seven did not develop a predictive model, 27‐33 in four the outcome to be predicted was not mortality, 34‐37 in another four they did not use their own data, 38‐41 two evaluated only one specific microorganism and not sepsis in general, 42,43 and one applied Machine Learning techniques, 44 which were not considered in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Further analyses will also be needed to delineate if the association of total caspases-3 and -9 with sepsis or mortality, might actually reflect an active or cleaved form induction. Assessing a “lymphocyte apoptosis model”, higher lymphocyte apoptotic percentages and lower HLA-DR expression independently predicted mortality in septic patients 56 . Moving the sepsis field onwards, this multicenter study’s findings could be taken into consideration and open up the way for future research on apoptotic/antiapoptotic biomarkers implicated in sepsis outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that in 2017, the percentage of admissions to the ICU caused by sepsis is ~25% and is associated with a mortality rate >50% worldwide (2,4). Although the precise pathophysiology of sepsis remains unclear, increasing evidence has indicated that it may move from an early hyper-inflammatory phase characterized by systemic inflammation induced by the excessive release of pro-inflammatory factors, followed by a late immuno-suppressive phase, characterized by the apoptosis of immune cells (including monocytes and lymphocytes) (5,6). Furthermore, apoptosis that occurs in the cells of tissues in the site of primary infection during sepsis can result in microvascular dysfunction, which subsequently leads to organ failure (7,8).…”
Section: Introductionmentioning
confidence: 99%